Local Government and Migrants Face to Face: Critical Nodes and Policies for Recognition - Thayer Correa, Luis Eduardo; Durán Migliardi, Carlos (Revista del CLAD Reforma y Democracia, 2015)
The purpose of this research is to identify the critical nodes of the process of incorporation of Latin American and Caribbean migrants to a local context, and identify the strategic priorities to guide migration policies from the municipal government. The proposal is based on the theory of recognition as a complementary but wider approach to the intercultural approach as a basis of local public policies. First, the work discusses the theoretical assumptions that this public policy assumes: human rights as the basis of citizenship, the centrality of the local and democratic governance as an approach. Secondly, it identifies the critical nodes in the process of incorporation of migrants and refugees in four dimensions: health, education, housing and employment. Finally, it is concluded that the implementation of migration policies at the local level, faces challenges in five strategic areas: information on rights, participation and politicization of migrants, education and awareness of the native population and mediation for coexistence. The fieldwork, conducted in Quilicura, Santiago of Chile, is presented as a resource for addressing the challenges for local governments towards the presence of migrants groups in the communal context.